2018
DOI: 10.1016/j.automatica.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Particle filters for partially-observed Boolean dynamical systems

Abstract: Partially-observed Boolean dynamical systems (POBDS) are a general class of nonlinear models with application in estimation and control of Boolean processes based on noisy and incomplete measurements. The optimal minimum mean square error (MMSE) algorithms for POBDS state estimation, namely, the Boolean Kalman filter (BKF) and Boolean Kalman smoother (BKS), are intractable in the case of large systems, due to computational and memory requirements. To address this, we propose approximate MMSE filtering and smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 43 publications
(50 reference statements)
0
31
0
Order By: Relevance
“…Moreover, heuristic mathematical models and methodologies in probabilistic filtering and inference such as feedback-based information roadmap [11], filtering in presence of partial observation [12], [13],and adaptive uncertainty propagation for coupled multidisciplinary systems [14]have the potential to improve the robustness of the proposed framework against the uncertainties in dynamical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heuristic mathematical models and methodologies in probabilistic filtering and inference such as feedback-based information roadmap [11], filtering in presence of partial observation [12], [13],and adaptive uncertainty propagation for coupled multidisciplinary systems [14]have the potential to improve the robustness of the proposed framework against the uncertainties in dynamical environment.…”
Section: Introductionmentioning
confidence: 99%
“…And, the classical noise-suppressing frameworks for multilicative noise removal are total variation [15]- [23] wavelet [24]- [31] and linear/nonlinear diffusion [9], [32]- [35]. Some scholars have applied statistical theories to establish frameworks for noise estimation, and these approaches may promote further understanding on the denoising of ultrasonograms [36]- [38]. This work focuses on two frameworks, namely total variation (TV) and nonlinear diffusion, which have demonstrated higher performances in recovering critical image features.…”
Section: Introductionmentioning
confidence: 99%
“…Tarachand [2] demonstrated that the optimum efficiency of a screw mechanism depends upon the helix angle. Imani et al [3][4] solved the problem of stochastic control of gene regulatory networks and Partially-observed Boolean dynamical systems are a general class of nonlinear models. Ghoreishi et.…”
Section: Introductionmentioning
confidence: 99%